Religion and the politics of tolerance: how Christianity builds democracy - Eisenstein, Marie A. (Baylor Univ. Press, 2008)
The politics of tolerance -- Christian political tolerance in contemporary America -- What do Christian congregants say about themselves? -- Issue attitudes, religion and political tolerance -- Political intolerance : is it really not about religion?